Vitamin C Cytotoxicity and Its Effects in Redox Homeostasis and Energetic Metabolism in Papillary Thyroid Carcinoma Cell Lines - Laura Tronci; Gabriele Serreli; Cristina Piras; Daniela Virginia Frau; Tinuccia Dettori; Monica Deiana; Federica Murgia; Maria Laura Santoru; Martina Spada; Vera Piera Leoni; Julian Leether Griffin; Roberta Vanni; et al. (MDPI AG, 2021)
High-dose of vitamin C (L-ascorbic acid, ascorbate) exhibits anti-tumoral effects, primarily mediated by pro-oxidant mechanisms. This cytotoxic effect is thought to affect the reciprocal crosstalk between redox balance and cell metabolism in different cancer types. Vitamin C also inhibits the growth of papillary thyroid carcinoma (PTC) cells, although the metabolic and redox effects remain to be fully understood. To shed light on these aspects, PTC-derived cell lines harboring the most common genetic alterations characterizing this tumor were used. Cell viability, apoptosis, and the metabolome were explored by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test (MTT), flow cytometry, and UHPLC/MS. Changes were observed in redox homeostasis, with increased reactive oxygen species (ROS) level and perturbation in antioxidants and electron carriers, leading to cell death by both apoptosis and necrosis. The oxidative stress contributed to the metabolic alterations in both glycolysis and TCA cycle. Our results confirm the pro-oxidant effect of vitamin C as relevant in triggering the cytotoxicity in PTC cells and suggest that inhibition of glycolysis and alteration of TCA cycle via NAD+ depletion can play an important role in this mechanism of PTC cancer cell death.